Motor cannery tender RED ROVER in waters off Port Moller, ca. 1912 - Thwaites, John E. (John Edward), 1863-1940 (1912)
Caption on image: The Red Rover, Port Moller, Alaska PH Coll 247.923 Port Moller is a village in southwest Alaska. It is located on the Alaska Peninsula at the entrance of Port Moller Inlet (20 mi long) of Bristol Bay on the Bering Sea. Primary industries are fishing and fish canning. The RED ROVER was built in 1913 for Pacific American Fishers